The role of tenure security in farmers' decision-making on investment in improved seeds: Insights from mental models - Lisa Murken; Kati Krähnert; Karlijn Van den Broek; John Adriko; Christoph Gornott (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
This paper applies a mental model approach to study the role of tenure security in farmers' decisionmaking on agricultural investment in Uganda. We investigate the role that both perceived tenure security and formal land rights, measured by the possession of land certificates, play. Our focus is on investment in improved seeds, a widely applied strategy in agricultural development and climate change adaptation. The study design leverages the roll-out of a large land demarcation and registration project, which creates exogenous variation in farmers' tenure security. Results show that, in contrast to expectations derived from economic theory, tenure security plays only a minor role in farmers' decision-making process to invest in improved seeds. Out of 15 potential factors determining a farmer's investment decision, both perceived tenure security and possession of a land certificate are among the least chosen factors, regardless of whether or not households participated in the land registration project. A heterogeneity analysis reveals that female-headed households value formalized land rights more than male-headed households. – – Diese Studie untersucht mit einem Mental Model-Ansatz, welchen Einfluss die Sicherheit des Landbesitzes bei der Entscheidungsfindung über Agrarinvestitionen von Kleinbauern in Uganda hat. Wir analysieren die Rolle, die sowohl die wahrgenommene Eigentumssicherheit als auch formale Landrechte, gemessen durch den Besitz von Landzertifikaten, spielen. Unser Schwerpunkt liegt auf Investitionen in verbessertes Saatgut - einer weit verbreiteten Strategie in der landwirtschaftlichen Entwicklung und der Anpassung an den Klimawandel. Das Studiendesign nutzt die Einführung eines großen Landregistrierungsprojekts, das zu exogener Variation in der Sicherheit des Landbesitzes führt. Die Ergebnisse zeigen, dass im Gegensatz zu den aus der Wirtschaftstheorie abgeleiteten Erwartungen die Sicherheit des Landbesitzes im Entscheidungsprozess der Kleinbauern, in verbessertes Saatgut zu investieren, nur eine untergeordnete Rolle spielt. Von den 15 potenziellen Faktoren, die die Investitionsentscheidung eines Kleinbauern bestimmen, gehören sowohl die wahrgenommene Eigentumssicherheit als auch der Besitz eines Landzertifikats zu den am seltensten ausgewählten Faktoren. Dies ist unabhängig davon, ob Haushalte an dem Landregistrierungsprojekt teilgenommen haben oder nicht. Eine Heterogenitätsanalyse zeigt, dass von Frauen geführte Haushalte formalisierten Landrechten eine wichtigere Rolle beimessen als von Männern geführte Haushalte.
Keywords: Q12; Q15; 330; Agricultural investment; decision-making; land titles; mental models; tenure security